(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
Leadership skills are fundamental for success in various spheres of life. Nurturing these abilities in children can have a positive impact on their future. This article aims to explore effective strategies to foster leadership qualities in children, emphasizing their developmental stages and practical applications.